2017
DOI: 10.1007/s00520-017-3703-y
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of same-day versus next-day administration of long-acting granulocyte colony-stimulating factors for the prophylaxis of chemotherapy-induced neutropenia: a systematic review

Abstract: Data from multiple publications support administration of pegfilgrastim at least 1 day after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 28 publications
2
32
0
3
Order By: Relevance
“…Based on clinical trial data, the panel recommends that pegfilgrastim be administered the day following myelosuppressive chemotherapy. 65 The rationale for not giving same-day pegfilgrastim is the potential for exacerbation of neutropenia resulting from stimulation of hematopoietic progenitor cells at the time of cytotoxic chemotherapy active in dividing cells, resulting in loss of the progenitors. 65,66 Based on review of these data, the panel endorsed the next-day administration of pegfilgrastim biosimilars.…”
Section: Nccn Recommendations For Management Of Fnmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on clinical trial data, the panel recommends that pegfilgrastim be administered the day following myelosuppressive chemotherapy. 65 The rationale for not giving same-day pegfilgrastim is the potential for exacerbation of neutropenia resulting from stimulation of hematopoietic progenitor cells at the time of cytotoxic chemotherapy active in dividing cells, resulting in loss of the progenitors. 65,66 Based on review of these data, the panel endorsed the next-day administration of pegfilgrastim biosimilars.…”
Section: Nccn Recommendations For Management Of Fnmentioning
confidence: 99%
“…65 The rationale for not giving same-day pegfilgrastim is the potential for exacerbation of neutropenia resulting from stimulation of hematopoietic progenitor cells at the time of cytotoxic chemotherapy active in dividing cells, resulting in loss of the progenitors. 65,66 Based on review of these data, the panel endorsed the next-day administration of pegfilgrastim biosimilars. Administration of pegfilgrastim or pegfilgrastim biosimilars up to 3 to 4 days after myelosuppressive chemotherapy is also reasonable based on trials of filgrastim.…”
Section: Nccn Recommendations For Management Of Fnmentioning
confidence: 99%
“…Similar findings were reported in follow-up studies using private healthcare claims data spanning 2010-2015 (OR ¼ 1.3, 95% CI 1.2-1.4) and using Medicare claims data (OR ¼ 1.3, 95% CI 1.2-1.4) 64,65 . A recent systematic review of the literature on this topic concluded that the literature supports "administration of pegfilgrastim to patients at least 1 d after the completion of a chemotherapy cycle" 66 .…”
Section: The 2010smentioning
confidence: 99%
“…In our study, we prescribed long-acting G-CSF according to the instruction booklet with 6 mg at 48 hours after chemotherapy. Such administration was reasonable according to a systematic review27 and consensus guidance recommendations 28. Patients who received pegfilgrastim on the day after chemotherapy had less severe and shorter suppression of the ANC than patients who received pegfilgrastim on the same day as chemotherapy 29.…”
Section: Discussionmentioning
confidence: 99%